THE RIGHT TO HUMAN SECURITY IN THE NEW DEMOCRACIES OF THE EUROPEAN UNION - Alina, Manolescu Angela (Anales Universitatis Apulensis Series Jurisprudentia; No 16 (2013): ANNALES UNIVERSITATIS APULENSIS - SERIES JURIPRDENTIA, 2013)
The issue of security is one of the most debated in the last decade. It is expected to play a significant role in the dynamics of the geopolitical future but also in the new European constitutionalism. Globalization has expanded the scope and extent of the traditional threats to security, but also the asymmetric risks that undermine human security. In fact, human security is no longer a problem that remains within the state but goes beyond its borders. The international community can create a suitable legal framework to ensure the implementation of the right to human security within states. Keywords: issue of security, globalisation, threats to security, international community